KARAKTERISTIK TEH HIJAU DAUN GAHARU HASIL PENGERINGAN VAKUM - Mhd.Iqbal Nusa (Agrintech: Jurnal Teknologi Pangan dan Hasil Pertanian, 2020)
Extract of Agarwood leaf contained secondary metabolites compound with phytochemicaltest, it has characteristic of antioxidant.The objective of this research was determainvacuum drying performance with vacuum pressure and temprature combination attime ofdrying variation effect to quality of Agarwood leaf tea. This research was applied factorialcomplete random design with variation vacuum pressure and temprature combinations asfollows 30 kPa and 500C; 30 kPa and 600C; 40 kPa and 500C; 40 kPa and 600C;at variationtime of drying as 3, 4, 5, and 6 hour. Obsered parameter among others were water content,rendement,organolepticcolour,romaandtaste.Antioxidantactivitybaseonthedetermination of the IC50. Research results shaw that vacuum pressure and tempraturecombination at variationtime of drying effectto quality of Agarwood leaf tea that wasdifferenceonwatercontent,organolepticvalue,andactivitylevelofantioxidant.